Development of technology for culturing a cell line producing a single-domain antibody fused with the Fc fragment of human IgG1 - D. S. Polyansky; E. I. Ryabova; A. A. Derkaev; N. S. Starkov; I. S. Kashapova; D. V. Shcheblyakov; A. P. Karpov; I. B. Esmagambetov (Тонкие химические технологии)
Objectives. To develop an effective technology for the cultivation of Chinese hamster ovary (CHO) cells stably producing GamP2C5 antibody which is a component I of the GamCoviMab candidate drug for emergency prevention and therapy of  infection caused by SARS-CoV-2 virus; to select optimal cultivation parameters and to scale this technology in production.Methods. The study was performed on CHO GamP2C5 (clone 78) cell culture, producing a single-domain antibody fused to the Fc fragment of human IgG1 GamP2C5. Different culture media and supplements were used. Cells were cultured in Erlenmeyer flasks, Biostat® RM 20 wave-mixed bioreactor, Ambr® 250 mini bioreactors, STR 200 stirred-tank bioreactor.Results. Using molecular-genetic and biotechnological methods, a stable clone producer of CHO GamP2C5 antibody, clone 78, was obtained. Then a technique was worked out for the cultivation of the obtained clone producer on different culture media. The most suitable cultivation regimes, culture media, and optimal supplements were selected. This technology was tested in laboratory conditions in a 10-L reactor, and then successfully scaled up for production at the MedGamal Branch of the Gamaleya National Research Center for Epidemiology and Microbiology.Conclusions. This study demonstrates the fundamental feasibility of developing and scaling up a culture technology, in order to produce a drug based on a modified single-domain antibody with virus neutralizing activity against different strains of SARS-CoV-2 virus.